NUCLEAR MEDICINE IN HIGHER EDUCATION INSTITUTIONS OF THE REPUBLIC OF UZBEKISTAN: CURRENT STATUS AND PROSPECTS (Academicia Globe: Inderscience Research, 2022)
The quality and effectiveness of teaching any subject depends on the scale of application of modern teaching methods in this area and the equipment of the clinical bases of higher educational institutions. The training of personnel with relevant knowledge, skills and competencies is also important in the field of nuclear medicine to provide optimally safe medical services and conduct quality research. Modern nuclear medicine consists of departments of radionuclide diagnostics and radionuclide therapy. The article considers and analyzes the current state of training in the republic, applying radionuclide methods in the examination and therapy of organs and systems of the human body. The article considers and analyzes the current state of training in developed countries and the Republic of Uzbekistan, working in the field of examination and therapy of organs and systems of the human body by radionuclide methods.